Disruptive strategic innovation plan for a university using "The house of quality" - Figueroa Donayre, Edgardo Martin (2023)
A strategic plan for innovation is an essential tool for any academic institution. This disruptive strategic plan for innovation maximizes the value and benefits for public and private institutions using the logical framework and the house of quality. With the logical framework of action, the input data for planning is clear, the rest of the activities of the house of quality (product design, process design and process control) are direct. The house of quality is the most effective technique to understand and even quantify the value of proposals. In addition, applied to a university, it ensures the obtaining of funds (money) that support and promote the development of innovation by prioritizing the voice of the customer (Innovate).